Douglas C. Harr letter to Nicholas S. Halmi regarding additional spring bird sightings, May 29, 1979 - Harr, Douglas C.et al (1979)
Letter from Douglas C. Harr to Nicholas S. Halmi regarding additional spring bird sightings in northwest Iowa, May 23, 1979. Sightings of Bell's Vireo and Upland Sandpiper are underlined in red. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1979. Epson - sheet feed/flatbed